Pengaruh Administrasi Perpajakan, Pelayanan Pada Wajib Pajak, Sanksi Pajak, Dan Insentif Pajak Terhadap Kepatuhan Wajib Pajak Bumi Dan Bangunan (Studi Kasus Pada Kecamatan Kartoharjo Kota Madiun) - Syarifah Ratih Kartika Sari; Aris Siswanto (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
This study aims to determine the effect of tax administration, services to taxpayers, tax sanctions and tax incentives on land and building tax compliance. This research includes quantitative research. The population in this study were taxpayers for Land and Building Tax in Kartoharjo District, Madiun City, determining the number of samples in this study using the Slovin formula with a maximum tolerable error rate of 10% so that 100 primary data can be obtained in the form of a questionnaire. Data analysis using multiple linear regression. The results of this study indicate that service to taxpayers and tax sanctions have a positive and significant effect on taxpayer compliance, while tax administration and tax incentives do not have a positive and significant effect on taxpayer compliance. Suggestions in further research are that it is necessary to hold counseling about the importance of paying taxes and the government creates a mobile application that contains information about land and building taxes, the government collaborates with minimarkets, postal or virtual payment applications to open land and building tax payment services so that it can make it easier for taxpayers to make payments, the government increases fines for taxpayers who violate it so that there is a more deterrent effect.